The Antarctic Subglacial Lake Vostok Glaciology, Biology and Planetology - Zotikov, Igor A. (Geophysical Sciences, 2006)
The first book on the subject, this monograph examines the phenomenon of a huge sealed, freshwater lake, isolated from the rest of the world by kilometers' thick ice. The existence of melting ice at the bottom of the huge Vostok Lake has served as a model and inspired the team planning the Galileo space craft to gather data on the ice sheet of the Jupiterian moon Europa. The book provides interpretation of, and calculations for, stimulating factors for possible melting and a huge lake's existence at the bottom of the Martian ice sheets.